Foreign phase inclusions in Ti-sapphire grown in a carbon-containing medium - Vyshnevskiy, S.D.; Kryvonosov, Ye.V.; Lytvynov, L.A. (Functional Materials, 2006)
The effect of carbon-containing growth medium on the character and formation features of foreign phase inclusions in Тi-sapphire has been studied. The crystals so grown may include both micrometer-sized (2 to 17 µm) and submicrometer-sized (about 100 nm) inclusions. The specifically cut micrometer-sized inclusions have been shown to be pores. The shape and orientation of submicrometer-sized inclusions in Тi-sapphire have been studied. А formation mechanism has been suggested for submicrometer-sized inclusions containing excess aluminum ant its suboxides. The inclusions are formed in solid phase in the course of phase transition at the crystallization front as a result of the crystal lattice supersaturation with anionic vacancies. Those defects are collapsed under the crystal high-temperature heat treatment due to uniaxial compressive stresses. Исследовано влияние углеродосодержащей среды выращивания на характер и особенности формирования инофазных включений в Тi-сапфире. Установлено, что эти кристаллы могут содержать: микронные (2...17 мкм) и субмикронные (около 100 нм) включения. Показано, что микронные включения, имеющие характерную огранку, являются порами. На основании индикатрис оптического рассеяния исследована форма и ориентация субмикронных включений в Тi-сапфире. Предложен механизм формирования субмикронных включений, содержащих избыточный алюминий и его субокислы. Включения формируются в твёрдой фазе в процессе фазового перехода на фронте кристаллизации как результат пересыщения кристаллической решётки анионными вакансиями. Эти дефекты разрушаются в результате высокотемпературной термообработки кристаллов под действием одноосных сжимающих напряжений. Дослiджено вплив вуглецевого середовища кристалiзацiї на характер i особливостi утворювання iнофазних включень в Тi-сапфiрi. Встановлено, що цi кристали можуть мiстити: мiкроннi (2 17 мкм) i субмiкроннi (менше 70 нм) включення. Показано, що мiкроннi включення є порами i мають характерне ограновування. На пiдставi аналiзу iндiкатрiси оптичного розсiяння дослiджена форма i орiєнтацiя субмiкронних включень в Тi-сапфiрi. 3апропоновано механiзм формування субмiкронних включень, якi є зародками пор i утворюються в твердiй фазi в процесi фазового переходу на фронтi кристалiзацiї як результат пересищення кристалiчної решiтки анiонними вакансiями. Встановлено, що цi дефекти руйнуються в результатi високотемпературної термообробки кристалiв пiд дiєю одноосних стискуючих напруг.